Valorization of palm tree (Phoenix dactylifera L.) leaves from harsh weather climate by silage using endogenous lactic acid bacteria, and application of MALDI-TOF MS for study of populations dynamics - Muhammad Zaid Jawaid (17807630) (2023)
Preservation of green palm leaves by silage preserves them as green feed in addition to the added value of probiotics and prebiotics. In this work, the characterization of fresh palm tree leaves was performed. The isolation of local lactic acid bacteria allowed selection of 4 isolates for the silage of the palm tree leaves. Dairy feed was used to enrich the leaves silage with the necessary nutrients. Lactobacillus paracasei and Pediococcus acidilactici were found to be dominating their respectively inoculated silages. The high occurrence of LAB found in the spontaneous silages of the palm tree leaves mixed with dairy feed is a good indication that ensiling palm tree leaves can support the growth of LAB and produce good-quality silage. However, a combination of the process by following the population dynamics using MALDI-TOF MS allowed the selection of the appropriate LAB strain, which is a new approach for application of silage. Other Information Published in: Bioresource Technology Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biteb.2023.101408